2020
DOI: 10.3390/ijms21197334
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in Cancer Cell Response to Nucleolar and Endoplasmic Reticulum Stress

Abstract: Eukaryotic cells are exposed to many internal and external stimuli that affect their fate. In particular, the exposure to some of these stimuli induces stress triggering a variety of stress responses aimed to re-establish cellular homeostasis. It is now established that the deregulation of stress response pathways plays a central role in cancer initiation and progression, allowing the adaptation of cells to an altered state in the new environment. Autophagy is a tightly regulated pathway which exerts “housekee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…Autophagy plays a role as a pro-survival mechanism for drug resistance [ 36 ]. We have recently demonstrated that the chemoresistance observed in uL3∆HCT 116 p53−/− cells might depend on the higher autophagic flux displayed by this cell population [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy plays a role as a pro-survival mechanism for drug resistance [ 36 ]. We have recently demonstrated that the chemoresistance observed in uL3∆HCT 116 p53−/− cells might depend on the higher autophagic flux displayed by this cell population [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in established tumors, it may act as a pro-survival pathway during stress conditions like nutrient deprivation, hypoxia, and cancer therapeutic treatment. Moreover, the inhibition of autophagy has been shown to prevent resistance of cancer cells to chemotherapy [ 36 ]. Recently, we have shown that resistance to drugs caused by uL3 depletion in p53-deleted colon cancer cells was due to autophagy induction [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…eL19 (L19) also activates the UPR, sensitizing breast cancer cells to ER stress-induced cell death, but the mechanism by which eL19 exerts this effect has not been fully elucidated [ 79 ]. More recently, transcriptomic RNA seq analysis of colon cancer cells devoid of p53 and stably silenced of uL3 has evidenced the activation of the UPR pathway, providing evidence of uL3 involvement in the regulation of this process [ 80 , 81 ].…”
Section: Role Of Ribosome Biogenesis In Neoplastic Transformationmentioning
confidence: 99%
“…The UPR and autophagy are interconnected and, recently, a link between the altered expression of some CRPs and autophagy modulation has emerged. Several stresses induced by mutations or deficiency of some CRPs may lead to autophagy induction in different cell types [ 81 ]. To date, in breast and ovarian cancer cell lines, the depletion of RPs such as uL10, RPLP1 and RPLP2 causes an increase in autophagic occurrence [ 82 ], whereas RPS27L silencing causes the blockage of this process via the mammalian target of rapamycin complex 1 (mTORC1) inactivation [ 83 ].…”
Section: Role Of Ribosome Biogenesis In Neoplastic Transformationmentioning
confidence: 99%
See 1 more Smart Citation